(untitled) (Pedagogical Horizons, 2022)
The article reports on the concept, background and experiences from the project StEOP+ | Practice of studying launched in WS19 at the Institute of Education of the University of Vienna. The low examination activity of the study beginners as well as the high drop-out rate despite positive examination successes gave reason to assume, that students of educational science are interested in their studies, but find little opportunity to discuss learning contents and to clarify questions of academic socialization. As a solution, Courses of the StEOP+ were constituted as „discussion rooms“ in which subject-specific learning dynamics can take place without instructing the independence of the students for their studies. The results of the project show that success and examination rates were paradoxically achievable because the learning processes taking place were not aligned with them. This result is finally discussed with regard to specifics of introduction to educational studies as well as in the context of institutional framework conditions.